Fabrication of nano-particle reinforced metal matrix composites - Pramanik, Alokesh; Littlefair, G. (Trans Tech Publications Inc, 2013)
Nanoparticle reinforced metal matrix possess much better mechanical properties over microparticle reinforced metal matrix composites as well as corresponding monolithic matrix materials. However, the fabrication methods of nanoparticle reinforced metal matrix composites are complex and expensive. This paper investigates and discusses the mechanisms of all the fabrication process, such as powder metallurgy, liquid metallurgy, compocasting and hybrid methods, available in the literature. This gives an insight on challenges associated with different processes and ways to improve the fabrication processes. It is found that modified traditional fabrication processes are mainly applied for these materials. The main problem is to achieve reasonably uniform distribution of nanoparticle reinforcement in the methods other than mechanical alloying when the volume or weight percent of reinforcement is higher (> 1%).